Tradisi Mangolat Ditinjau Dari Hukum Islam - Leha Elisa Harahap; Ikhwanuddin Harahap; Syapar Alim Siregar (Jurnal El-Thawalib, 2022)
Mangolat boru is an event to confront the bride and groom before the bride's departure to the namboru's house (in-law) which is carried out by the namboru's son from the bride as a farewell so that there is a pangolat wage or money. Pangolat money will be given by the men to the namboru from the women. the wages or pangolat money given by the groom is not enough, so the namboru child of the bride continues to hold and ask for more mangolat wages to the groom. In addition to slowing down, sometimes the time of the mangolat jam approaches the Maghrib call to prayer, which is where the implementation of this mangolat still continues. The purpose of the study was to find out how Islamic law reviews the mangolat tradition in marriage customs in the Bondar flower family, Sipirok district, South Tapanuli district and to find out the implementation of the mangolat tradition in the community of Bunga Bondar village. This type of research is field research. Research conducted in collecting data on phenomena that occur, is natural and scientific. The data collection of this research uses observational field studies, interviews, as well as documentation and libraries, and uses a systematic discussion. The results revealed in the thesis entitled Mangolat Tradition in Marriage Customs in the Bunga Bondar Village, Sipirok District, South Tapanuli Regency is that the mangolat custom tradition carried out by the community has been carried out for generations in various generations, this mangolat event is the last event in the implementation of the mandatory custom. carried out in a wedding ceremony, with that wages or money pangolat will always be a complement to the implementation of the mangolat pickle, where the mangolat event will take a lot of time so that the departure of the bride and groom will take a long time due to the implementation of this mangolat event.